The Effectiveness of Peat-AC Composite Adsorbent in Removing SS, Colour and Fe from Landfill Leachate - Rosli, Mohd Arif; Daud, Zawawi; Awang, Halizah; Abdul Latiff, Ab Aziz; Zainorabidin, Adnan; Abdul Halim, Azhar (International Journal of Integrated Engineering, 2017)
Adsorption is a commonly used method for the removal of such various pollutants from aqueous solutions. Nowadays, due to cost-effectiveness, the adsorbent should be economical and cheaply available in abundance and it should require minimal for discharge into water bodies. This study was undertaken to investigate the efficiency of activated carbon (AC) to partially replace with peat as an inexpensive adsorbate composite medium for removing suspended solid (SS), colour and iron (Fe) from landfill leachate. The process of identifying the optimum composition of the composite adsorbent was carried out using batch technique. It shaken for 120 minutes with 200 rpm at pH 7. The optimum ratio of peat and AC had been chosen as 2.0:2.0 for SS and color while 2.5:1.5 for Fe. The value of the removal percentage for SS, colour and Fe were 71.6%, 74.4% and 79.6% in respectively. This indicates that peat can be used as a cost-effective medium to partially substitute of commercially AC in the composite for SS, colour and iron removal at a considerably lower cost.